2022
DOI: 10.3390/economies10040078
|View full text |Cite
|
Sign up to set email alerts
|

The Volatility of Rupiah Exchange Rate Impact on Main Commodity Exports to the OIC Member States

Abstract: This study analysed the impact of the volatility of the rupiah exchange rate on four main commodities exported from Indonesia to six member countries of the Organisation of the Islamic Cooperation (OIC) (Saudi Arabia, Malaysia, Pakistan, United Arab Emirates, Turkey, and Bangladesh). The study employed monthly data spanning from January 2007 to December 2019 and the EGARCH method to obtain exchange rate volatility, while the ARDL method was used to model both the short-run and long-run impact of exchange rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…The 1998 emergency was not only influenced by elementary economic aspects, but it was also influenced by speculative activities on the exchange rate of the Rupiah against the US Dollar which at that time was still weak in supervision from Bank Indonesia as the monetary authority and was also influenced by market sentiment because at that time Pak Suharto (President of the Republic of Indonesia) is sick, and politically unstable (many demonstrations from students) and negative sentiment from neighboring countries, namely Thailand, which experienced an economic crisis first, where at that time the Thai government declared its inability to pay its debts. The results of this study are supported by research conducted by Handoyo R. D. Sari A. D. P. in 2022 (Handoyo, Sari, Ibrahim, & Sarmidi, 2022).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The 1998 emergency was not only influenced by elementary economic aspects, but it was also influenced by speculative activities on the exchange rate of the Rupiah against the US Dollar which at that time was still weak in supervision from Bank Indonesia as the monetary authority and was also influenced by market sentiment because at that time Pak Suharto (President of the Republic of Indonesia) is sick, and politically unstable (many demonstrations from students) and negative sentiment from neighboring countries, namely Thailand, which experienced an economic crisis first, where at that time the Thai government declared its inability to pay its debts. The results of this study are supported by research conducted by Handoyo R. D. Sari A. D. P. in 2022 (Handoyo, Sari, Ibrahim, & Sarmidi, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…Meanwhile, the development burden implies that the obligation is considered a financing option that through various special and monetary calculations is deemed ready to provide benefits (Muktiyanto & Aulia, 2019). Research on the relationship between foreign debt and the volatility of the rupiah exchange was conducted by Handoyo R. D. Sari A. D. P. in 2022 (Handoyo et al, 2022).…”
Section: Foreign Debtmentioning
confidence: 99%
“…Findings indicate that volatility asserts a significant positive influence on manufacturing export in the long run, and no evidence of a significant effect in the short run. Similarly, in the case of Indonesian exports to the Organization of the Islamic Cooperation (OIC) member states, [ 15 ] observed that exchange rate volatility negatively affects the export of some selected commodities export in both the short run and long run.…”
Section: Review Of Literaturementioning
confidence: 99%
“…HS-Code 4 digits level). The only exceptions are [ 15 , 16 ] among others, who analyzed the influence of volatility on HS-Code 2-digit level products. These studies had only focused on HS-Code 2 digits level products while the present study aims to bridge a gap by exploring the volatility of exchange rate effect on HS-Code 4-digit level products that are more disaggregated than the 2-digit products.…”
Section: Introductionmentioning
confidence: 99%
“…[ 57 ] shows that exchange rate volatility has a negative impact on Canadian and Japanese exports to the United States and on Australian exports to the world. In the Organization of Islamic Cooperation (OIC) [ 58 ], also find the negative effect of exchange rate volatility on main export commodities both in the short and long run.…”
Section: Literature Reviewmentioning
confidence: 99%